2019
DOI: 10.1002/aelm.201901002
|View full text |Cite
|
Sign up to set email alerts
|

Bar‐Coated Organic Thin‐Film Transistors with Reliable Electron Mobility Approaching 10 cm2 V−1 s−1

Abstract: Currently, a considerable number of solution-processed high mobility p-type OTFTs have been obtained. [4-8] However, the achievement of high performance n-type OTFTs via solution processing is still challenging, yet important for the construction of organic circuits such as complementary metal-oxide-semiconductor (CMOS)-like circuits. [9-12] Reviewing of recent development has demonstrated that the highest reliable electron mobility from solution-processed OTFTs is 7.16 cm 2 V −1 s −1 to date. [11] To enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…The degree of polymer alignment has proven to have a strong dependence on the coating speeds, and thus a remarkable enhancement in charge-transport anisotropy can be achieved. [24][25][26][27][28] Moreover, the choice of solvent plays an important role in determining device performance as well. Many previous reports have demonstrated the formation of uniaxially aligned nanofibrillar film morphologies by utilizing certain (mixture) solvents Aggregation-structure formation of conjugated polymers is a fundamental problem in the field of organic electronics and remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of polymer alignment has proven to have a strong dependence on the coating speeds, and thus a remarkable enhancement in charge-transport anisotropy can be achieved. [24][25][26][27][28] Moreover, the choice of solvent plays an important role in determining device performance as well. Many previous reports have demonstrated the formation of uniaxially aligned nanofibrillar film morphologies by utilizing certain (mixture) solvents Aggregation-structure formation of conjugated polymers is a fundamental problem in the field of organic electronics and remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Based on high conductivity and high surface work function (WF), Au electrodes are beneficial to the outstanding performance of p-type OTFTs, and in some reports, modified Au electrodes are even used in n-type OTFTs. [7][8][9] However, it is well known that Au electrodes are extremely expensive, which would greatly hinder the development of practical applications.Indium tin oxide (ITO), the most commonly used organic light-emitting diodes (OLEDs) anode material, has high conductivity and relatively cheap price, while its work function (≈4.7 eV) is lower than the ionization potentials of most p-type OSC. [10] To reduce the barrier height and facilitate the hole injection, various ITO modification methods have been made in OLEDs and organic photovoltaics (OPVs), such as self-assembling, plasma treatment, ultraviolet (UV)-ozone treatment, surface doping and so on.…”
mentioning
confidence: 99%
“…It has been demonstrated that PEIE modification can effectively lower the work function of Au, and then facilitate efficient electron injection and block the hole injection from electrodes to the semiconducting layer. 70,71 Accordingly, all OTFTs with PEIE interlayer exhibited pure electron transport characteristics with much lower V T (Fig. 3 and Fig.…”
Section: Resultsmentioning
confidence: 93%